Mentoring: Helping Youth Make a Difference in STEM - Angelia Reid-Griffin (Journal of Education in Science, Environment and Health)
Mentoring is a life-long approach to building positive, supportive relationships, self-confidence and increasing academic performance. In this article, I present how a college-based summer camp, designed to engage youth in increasing interests in STEM, Healthcare, and Teacher education, by helping youth build self-confidence and career interests through a Vertical Mentoring model. An exploratory case study approach is used to gain insight into how the model shaped youths’ interactions in learning concepts in STEM. Middle school participants completed a self-efficacy scale and career inventory of perceptions, learning and academic interests. Middle school youth and mentors provided insight on their attitudes, interests and overall satisfaction about the program experiences. Findings interpreted based on the tenets of positive youth development implemented and provides an anchor for additional mentoring studies. Self-efficacy results indicated that students were motivated in utilizing social resources and supports but rarely sought assistance from others. Drawing from the interview responses from mentees and mentors, the Vertical mentoring model afforded youth increased social interactions and opportunities in learning about STEM concepts outside of their home and school settings. Thus, students with no interest in STEM prior to the college-based camp did benefit positively from the STEM mentoring opportunity.